Decommissioning and demolition of a dicalcium phosphate plant: aspects of radiological protection and safety - Romão Trindade; Ana Sofia Marques; Ana Cristina Albuquerque; João Schiappa; Ana Margarida Matos; Joana Moreira; J. Narciso; D. Lopes (Brazilian Journal of Radiation Sciences, 2024)
The detection of ionising radiation in materials from the decommissioning of a dicalcium phosphate plant meant that this whole operation had to be overhauled in terms of radiological protection and safety. Thus, an operations plan was drawn up that included: initial training for all workers involved, measurements of dose rates and a set of analyses by gamma and alpha spectrometry. Samples of "dry sludge" and debris were analysed for the identification and quantification of the radionuclides present, samples of workers' urine were analysed for the detection of any internal contamination, samples of washing water and air filters were analysed for the detection and control of any radioactive atmospheric contamination. In addition, individual dosimeters were distributed to workers. The extent of contamination was identified and the areas where higher values were detected were properly marked. From the results obtained (radiation dose rates and activity concentrations), it was possible to establish categories and separate the contaminated materials according to their physical characteristics. After the plant decommissioning, the resulting waste with dose rates higher than the effective dose limits for the public was packed in big bags. These bags were divided in 3 groups according to the external radiation dose rates at contact. This segregation allowed the competent authority to release a significant number of big bags from regulatory control. The remaining big bags are stored in two metal containers subject to regular radiological monitoring. The objective of this work is the presentation of a factual article where the methodology implemented to deal with this situation, which had never occurred in Portugal, is described, having only the Portuguese legislation as a reference.